Evidências de validade de conteúdo e usabilidade de um recurso educacional digital (RED GAME- GAMI) para promoção da saúde mental infantil - Paiva, Felipe Moreira de (2024)
Digital Educational Resources are resources for learning and teaching processes. In health, these resources can be important tool for education and health promotion. Validation is the step which these resources are evaluated according to their purposes. There are a lot of features presented in validation instruments and they could be related to the content of the resource or about usability, which includes satisfaction, engagement, easy-to-use, frequency of use and acceptability by the users and health professionals. This thesis aims to validate a digital educational resource for children’s mental health promotion (RED GAME-GAMI) according to content validity and usability. It was performed a validation study, using 17 expert judges, professionals and researchers of children’s mental health area. For content analysis, it was used Content Validation Index (CVI), using an adapted instrument, and System Usability Scale (SUS), for usability analysis. For both tests, it was used Cronbach’s alpha to verify internal consistency between the judges. It were evaluated for content validity the domains objectives, structure and presentations and relevance of the game. Self-recognition, territory, support network, right to health and medication usage were evaluated in these domains. For usability, it were evaluated satisfaction, engagement, acceptability, frequency and easiness of use. For global CVI, the value was 0.91, representing a score for 0.972 in Cronbach’s alpha, and a SUS score from 0.85 (79.4-90.4), with 0.889 of Cronbach’s alpha. The results show an excellent concordance level for content and excellent level of usability for RED GAME-GAMI. Besides, there is a high internal consistency. RED GAME-GAMI seems to be an important tool with great potential of use to promote children’s mental health in mental health services.